PENANAMAN NILAI-NILAI NASIONALISME DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 2 WATES, KULON PROGO - Saefur Rochmat; Diana Trisnawati (Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to: (1) Outlining the history of the learning process in SMA Negeri 2 Wates, Kulon Progo, and (2) Describe efforts to inculcate nationalism in the teaching of history in SMA Negeri 2 Wates, Kulon Progo. The method used in this research is descriptive qualitative research method. The data collection is done through in-depth interviews, direct observation and recording of documents. The results showed that the teaching of history in SMA Negeri 2 Wates do in the classroom during school hours and outside the classroom takes place through extra-curricular activities. Teachers deliver material as specified in the curriculum with the methods and media that support student success. Planting the values of nationalism done in several ways, namely to integrate in subjects such as history subjects, and the subjects Civics. In addition, the values of nationalism is also implanted through habituation attitude in the school environment, such as mutual cooperation, courtesy, tolerance, and so on. Keywords: Nationalism, Teaching History, SMA Negeri 2 Wates.